Structural and magnetic changes induced by electron and ion irradiation on HOPG - Avila, Milagros (2015)
In recent decades, many studies reported magnetism in carbon-based materials. This phenomenon was attributed to structural defects within the sample. Many authors showed an increase of magnetization in HOPG (Highly Oriented Pyrolytic Graphite) induced by proton bombardment, meanwhile the effect of electronic irradiation on the magnetic behavior has been unattended till now. The aim of this work is to contribute to the understanding of defect-induced effects on the structural and magnetic properties of graphite. For this purpose, we performed experiments of irradiation on HOPG with two different impinging projectiles −electrons and ions. The structural characterization of the bombarded samples was carried out by Raman spectroscopy. On both irradiated samples we identify the D band, associated to the disorder induced by bombardment, with significantly distinct contributions depending on the projectile type. In order to interpret Raman results, a theoretical model proposed by Ferrari et al. was used to classify the generated defects. The relationship between the induced damage and magnetization was evaluated by magnetic characterization measurements with a SQUID (Superconducting Quantum Interference Device). Our results suggest that electron bombardment produces a higher change in the magnetic order compared to the magnetization induced by ion bombardment.